Quantity discrimination: Effect of number ratio over speed and accuracy - Formoso, Jesica (2016)
The ability to estimate and discriminate quantities is of early onset in the development and prior to the acquisition of a symbolic numerical system. The performance on tasks of discrimination is modulated by the number ratio that differentiates the sets, so that smaller reasons result in slower and less effective comparisons. The objective of the present study is to analyze the precision and speed by which 4 and 6 year old children discriminate between two quantities based on the number ratio that distinguishes them. Method: a discrimination task of non-symbolic quantities (ad hoc) was given to 60 children from 4 and 6 years old in the city of Buenos Aires, Argentina. A mixed ANOVA design was carried out to analyze the amount of hits and reaction times (RT) according to age, and the number ratio that differentiates the groups. The Bonferroni contrast test was used to detect the differences in hits and RT between each reasoning. Results: (a) children age 6 showed smaller RT and more hits than children age 4. This suggests that discrimination on the basis of quantities is undergoing a process of evolutionary development. (b) The greater the number ratio in the differentiation of the sets, the more effective the discrimination. This suggests that reason modulates performance regardless of the age of the subject. DOI: https://doi.org/10.24265/liberabit.2016.v22n1.02